Pengaruh Minat Belajar terhadap Hasil Belajar Matematika Siswa Kelas X SMA N 14 Semarang - Nila Mustika Ningrum; Heni Purwati; Ichsan Budi Lestari; Achmad Buchori (Departement of Mathematics Education, 2024)
This research has a unique intuitive effect on the influence of interest in learning on the mathematics learning outcomes of class This type of research is quantitative research with post facto methods. The population of this research is a selection of class X students which consists of 9 classes with each class numbering more or less 36 students. The sample used was class X-2, totaling 35 students, with the sample taken using the simple random sampling method. The data collection techniques used were questionnaires and thesis. Data analysis in this research uses simple linear regression analysis. Before carrying out a linear regression test, prerequisite tests are first carried out in the form of normality tests, linearity tests and homoscedidity tests. The research results show that the regression equation results ???? = 59.940 + 0.461???? which means that every one unit increase in the learning interest variable will result in an increase in mathematics learning outcomes of 0.461 units. Apart from that, interest in learning also has an influential contribution to mathematics learning outcomes of around 49.3%. This indicates that the increase or decrease in mathematics learning outcomes is influenced by interest in learning amounting to 49.3%, while the remaining 50.7% is influenced by other factors. So it can be concluded that interest in learning has a significant influence on the mathematics learning outcomes of class X students at SMA N 14 Seimarang in the 2023/2024 academic year.